The Implementation of Learning Model in Talking Stick by Using Short Story Text to Improve Students’ Reading Comprehension At SMP Negeri 15 TIKEP - Lisnawati Harun (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2018)
This Research is a class act that uses short story text thorough learning model of talking stick to improve students’ reading comprehension. This subject is class VII SMP NEGERI 15 Tidore Kepulauan 2017-2018 school year the sample of 12 students. This study to be implemented in one class, each cycle consisting of four components, namely: planning, implementation, observation, and reflection. Data were collected through taking video, observation sheet and field note on each cycle. Based on the results of research, teaching by using short story text through learning model of talking stick can improving students’ reading comprehension of the students class VII SMP NEGERI 15 TIKEP. The results of the research subjects to study of reading and understanding the meaning of short story text on the actions of the first cycle still there are 6 students who do not achieve mastery, while 6 other students have achieved mastery. In the second cycle action, and from 12 students who following the learning, all of them achieved mastery. Which means all of students in the second cycle have completed if the value measured by KKM 70.